Evaluation of allergenic protein profiles in three Chinese high-oleic acid peanut cultivars using NanoLC-Orbitrap mass spectrometry - Xinke Yang; Haochen Bai; Lijun Yin; Jin Wang; Wentong Xue; Xin Jia (Food Science and Human Wellness)
High oleic-acid peanuts are known for their pre-longed shelf-life and health benefit due to high content of oleic fatty acid. However, the allergenicity and allergenic protein profiles in Chinese high-oleic peanuts have yet to be studied. For this purpose, an Orbitrap Fusion mass spectrometry (MS)-based method that is feasible for identification of putative allergenic protein as well as semi-quantitation of five major allergen protein in three different Chinese high-oleic peanut cultivars (JH 13, JH 16 and JH 18) have been reported. Results show that three Chinese high-oleic acid peanut cultivars selected all contained highly allergenic proteins Ara h 1, Ara h 2, Ara h 3 and Ara h 6. The allergenic protein profiles of Chinese high-oleic acid peanut cultivars were very similar to that of conventional peanuts, but the allergenic protein subunits varied greatly among high-oleic peanuts. Additionally, a comprehensive peptide-filtering pipeline had been developed for identification of potential peptide markers in peanut allergen proteins. Through the peptide-filtering pipeline, three novel peptide markers, IVQIEAKPNTLVLPK, SSNPDIYNPQAGSLR and AQSENYEYLAFK surrogate to Ara h 1, Ara h 3 with high abundance, good MS response and highly reliability were identified, which can be used as candidate peptide markers for the detection of peanut allergens in different food matrices.